Bodies, Boundaries and Spirit Possession : Maroccan Women and the Revision of Tradition - Rausch, Margaret (Globaler lokaler Islam, 2015)
The social structures of Moroccan society have been changing in accordance with western models at an ever-growing rate. The role of Islam in sharing the burden of these changes and in narrowing the ever-expanding gap between modernity and tradition is exemplified by the folk-Islamic spirit possession practices presented in this study. By adjusting their vocation to ongoing processes of commercialization and professionalization and to the changing needs and expectations of their female clientele, traditional women seers have increasingly taken on the therapeutic task of helping women to resolve the growing number of inner and interpersonal conflicts in their daily lives.